Transcriptome analysis and exploration of genes involved in the biosynthesis of secoiridoids in Gentiana rhodantha - Zhang,Ting; Wang,Miaomiao; Li,Zhaoju; Wu,Xien; Liu,Xiaoli (PeerJ, 2023)
Gentiana rhodantha is a medicinally important perennial herb used as traditional Chinese and ethnic medicines. Secoiridoids are one of the major bioactive compounds in G. rhodantha. To better understand the secoiridoid biosynthesis pathway, we generated transcriptome sequences from four organs (root, leaf, stem and flower), followed by the de novo sequence assembly. We verified 8-HGO (8-hydroxygeraniol oxidoreductase), which may encode key enzymes of the secoiridoid biosynthesis by qRT-PCR. The mangiferin, swertiamarin and loganic acid contents in root, stem, leaf, and flower were determined by HPLC. The results showed that there were 47,871 unigenes with an average length of 1,107.38 bp. Among them, 1,422 unigenes were involved in 25 standard secondary metabolism-related pathways in the KEGG database. Furthermore, we found that 1,005 unigenes can be divided into 66 transcription factor (TF) families, with no family members exhibiting significant organ-specificity. There were 54 unigenes in G. rhodantha that encoded 17 key enzymes of the secoiridoid biosynthetic pathway. The qRT-PCR of the 8-HGO and HPLC results showed that the relative expression and the mangiferin, swertiamarin, and loganic acid contents of the aerial parts were higher than in the root. Six types of SSR were identified by SSR analysis of unigenes: mono-nucleoside repeat SSR, di-nucleoside repeat SSR, tri-nucleoside repeat SSR, tetra-nucleoside repeat SSR, penta-nucleoside repeat SSR, and hexa-nucleoside repeat SSR. This report not only enriches the Gentiana transcriptome database but helps further study the function and regulation of active component biosynthesis of G. rhodantha.
Keywords: G. Rhodantha; Transcriptome; Biosynthesis; Metabolism pathway; qRT-PCR; Secoiridoid